2002
DOI: 10.1073/pnas.102165699
|View full text |Cite
|
Sign up to set email alerts
|

Mayolenes: Labile defensive lipids from the glandular hairs of a caterpillar ( Pieris rapae )

Abstract: Larvae of the European cabbage butterfly, Pieris rapae (Pieridae), are beset with glandular hairs, bearing droplets of a clear oily secretion at their tip. The fluid consists primarily of a series of chemically labile, unsaturated lipids, the mayolenes, which are derived from 11-hydroxylinolenic acid. In bioassays with the ant Crematogaster lineolata, the secretion was shown to be potently deterrent, indicating that the fluid plays a defensive role in nature.chemical defense ͉ predation ͉ Lepidoptera ͉ Formici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 17 publications
1
34
0
Order By: Relevance
“…1 H-NMR-spectroscopic analyses of crude, unfractionated larval-secretion samples showed that the secretion consisted largely of the mayolenes described earlier (11). In addition, the spectra reproducibly showed several signals that appeared to belong to a lessabundant, previously unidentified component (Fig.…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…1 H-NMR-spectroscopic analyses of crude, unfractionated larval-secretion samples showed that the secretion consisted largely of the mayolenes described earlier (11). In addition, the spectra reproducibly showed several signals that appeared to belong to a lessabundant, previously unidentified component (Fig.…”
Section: Resultsmentioning
confidence: 81%
“…We had noted the fluid to contain a series of structurally labile linolenic acid derivatives, the mayolenes (6 in Fig. 3), which we demonstrated to be protective against ants (Crematogaster lineolata) (11). We have found pinoresinol itself to also be deterrent to ants (bioassay with Formica exsectoides), indicating that the compound could be part of the armamentarium of the larva.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Larval chemical defense in many pierid species is attributable to oily droplets attached to the tips of dorsal setae. Smedley et al (2002) showed that in Pieris rapae (L.) these droplets contain unsaturated lipids (mayolenes) that repel ants. Neophasia menapia larvae do not carry oily droplets on their setae (James & Nunnallee 2011) and may rely instead upon the prosternal gland for defense.…”
Section: Discussionmentioning
confidence: 99%
“…In other insects, similar dorsal glandular setae or spines bearing viscous, oily droplets that are not antimicrobial. In lepidopteran larvae and hemipteran nymphs the secreted substances provide a form of defence (Carver, 1991;Smedley et al, 2002;Shiojiri and Takabayashi, 2005;Schroeder et al, 2006) or help in the search for the host-plant (Takabayashi et al, 2000).…”
Section: Introductionmentioning
confidence: 99%